PENGARUH MODEL THINK PAIR SHARE TEMA EKOSISTEM SUBTEMA 1 BERBANTU MEDIA POKI TERHADAP HASIL BELAJAR SISWA KELAS V SDN PENGARADAN 02 BREBES - Sulistiyawati, Indah; Rustopo, Rustopo; Mudzanatun, Mudzanatun (JGK (Jurnal Guru Kita), 2019)
Abstract: Influence of Learning Snowball Throwing Assisted Media Puppet on Student Learning Result of Social Science Class IV SDN 01 Sidomulyo Kendal. The purpose of this study was to determine the effect of the Think Pair Share model on the theme of Subtitles 1 with the help of Poki media on the learning outcomes of the fifth grade students of SDN Pengaradan 02 Brebes. This type of research is quantitative with the experimental method and Pre-Experimental Design. The samples taken were all fifth grade students totaling 30 students using the Nonprobability Sampling technique in the form of saturated sampling. The results of the study showed that there were differences in learning outcomes between students who were learning with the Tree Teka-Puzzle (POKI) media-assisted Think Pair Share learning model with students learning with conventional learning models. Keywords: Think Pair Share Model, Media Tree Puzzle (POKI), Learning Outcomes Abstrak: Pengaruh Model Think Pair Share Tema Ekosistem Subtema 1 Berbantu Media Poki Terhadap Hasil Belajar Siswa Kelas V SDN Pengaradan 02 Brebes. Tujuan penelitian ini adalah untuk mengetahui pengaruh model Think Pair Share tema ekosistem subtema 1 berbantu media Poki terhadap hasil belajar siswa kelas V SDN Pengaradan 02 Brebes. Jenis penelitian ini adalah kuantitatif dengan metode eksperimen dan Pre-Eksperimental Design. Sampel yang diambil adalah seluruh siswa kelas V yang berjumlah 30 siswa dengan menggunakan teknik Nonprobability Sampling berbentuk sampling jenuh. Hasil penelitian menunjukkan bahwa terdapat perbedaan hasil belajar anatara siswa yang belajar dengan model pembelajaran Think Pair Share berbantu media Pohon Teka-teki (POKI) dengan siswa yang belajar dengan model pembelajaran konvensional. Kata Kunci: Model Think Pair Share, Media Pohon Teka-teki (POKI), Hasil Belajar